SOX2 Expression Is Regulated by BRAF and Contributes to Poor Patient Prognosis in Colorectal Cancer - Lundberg, Ida V. (Public Library of Science, 2014)
Sporadic colorectal cancer (CRC) is a common malignancy and also one of the main causes of cancer deaths worldwide. Aberrant expression of the transcription factor SOX2 has recently been observed in several cancer types, but its role in CRC has not been fully elucidated. Here we studied the expression of SOX2 in 441 CRC patients by immunohistochemistry and related the expression to clinicopathological and molecular variables and patient prognosis. SOX2 was expressed in 11% of the tumors and was significantly associated to BRAF(V600E) mutation, but not to KRAS mutations (codon 12 and 13). SOX2 positivity was correlated to poor patient survival, especially in BRAF(V600E) mutated cases. In vitro studies showed that cells expressing the constitutively active BRAF(V600E) had increased SOX2 expression, a finding not found in cells expressing KRAS(G12V). Furthermore, blocking downstream BRAF signalling using a MEK-inhibitor resulted in a decreased expression of SOX2. Since SOX2 overexpression has been correlated to increased migration and invasion, we investigated the SOX2 expression in human CRC liver metastasis and found that a SOX2 positive primary CRC also had SOX2 expression in corresponding liver metastases. Finally we found that cells overexpressing SOX2 in vitro showed enhanced expression of FGFR1, which has been reported to correlate with liver metastasis in CRC. Our novel findings suggest that SOX2 expression is partly regulated by BRAF signalling, and an increased SOX2 expression may promote CRC metastasis and mediate a poor patient prognosis.